Screening virulence factors of porcine extraintestinal pathogenic Escherichia coli (an emerging pathotype) required for optimal growth in swine blood. Issue 4 (5th October 2020) - Ma, Jiale; Cheng, Zhixin; Bai, Qiankun; Zhao, Kejie; Pan, Zihao; Yao, Huochun
Abstract: Porcine extraintestinal pathogenic Escherichia coli (ExPEC) is occurring with increasing frequency in China, which causes acute septicemia and sudden death in pigs leading to significant economic losses. Bacterial survival and even proliferation within host bloodstream are a common manifestation of a number of bacterial septicemias, including porcine ExPEC diseases. However, the underlying pathogenesis for this novel pathotype of ExPEC has not been explored deeply. Here, we used a conjunction with transposon mutagenesis to identify the mechanisms of bacterial fitness involved in optimal growth of porcine ExPEC in swine serum ex vivo under static culture. Our work identified 28 genes involved in nucleotide biosynthesis, extracellular polysaccharide biosynthesis, regulators Fur and FNR, acid/zinc resistance, and Deley‐Douderoff carbon metabolism that are required for the serum fitness. Subsequent functional analyses revealed that either interruption of de novo nucleotide biosynthesis or blocking of several extracellular polysaccharide biosynthesis including O2‐antigen, Lipid A‐core, and ECA significantly affect porcine ExPEC's growth in swine serum and proliferation in host bloodstream. Furthermore, the reasonable regulations of iron and anaerobic metabolisms in response to host stimuli by global regulators Fur and FNR also play key roles during systemic infection of porcine ExPEC. These findings provide compelling evidences that de novo nucleotide biosynthesis may enable porcine ExPEC to adapt to swine blood‐specific nutrient availability, and the effective assembly of O‐antigen, lipid A‐core, and ECA is required to resist the bactericidal activity of swine serum. These studies contribute to better understand the underlying mechanisms employed by porcine ExPEC to survive, grow in the swine bloodstream, and cause disease. These related factors may serve as therapeutic targets for countering or preventing ExPEC serum resistance in the clinic.